Successful Pregnancy following Mixed Double Embryo Transfer in a Patient with Variable Window of Implantation - Georgi Stamenov Stamenov; Dimitar Angelov Parvanov; Todor Angelov Chaushev (Hindawi Limited, 2018)
The process of embryo implantation is carried out during the receptive stage of the endometrium in the midluteal phase of the menstrual cycle, known as window of implantation (WOI). It has been assumed that the WOI is not a constant variable in all women and the determination of its displacement is of crucial importance, especially for patients with recurrent implantation failure (RIF). Furthermore, in rare cases it could have different duration and position in the menstrual cycle even in the same woman but during different periods. Here, we report a 37-year-old woman with RIF, who was previously classified as idiopathic but has now been diagnosed as having a variable WOI. This interpretation was done after the performance of immunohistochemical and histomorphological analyses of endometrial biopsies taken in the midluteal phase during three sequential menstrual cycles. In order to solve the problem with pinpointing a variable WOI, a specific type of embryo transfer, called mixed double embryo transfer (MDET), was done where one Day 3 and one Day 5 good quality embryos were transferred simultaneously 7 days after ovulation. A viable single pregnancy was confirmed by ultrasound scan and a healthy girl was born. This case showed a unique approach in overcoming the problem in RIF patients with variable WOI.